2007
DOI: 10.1207/s15324796abm3301_7
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of changes in diet, exercise, and stress management to changes in coronary risk in women and men in the Multisite Cardiac Lifestyle Intervention Program

Abstract: Improvements in dietary fat intake, exercise, and stress management were individually, additively and interactively related to coronary risk and psychosocial factors, suggesting that multicomponent programs focusing on diet, exercise, and stress management may benefit patients with CHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
91
2
15

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(112 citation statements)
references
References 54 publications
4
91
2
15
Order By: Relevance
“…These interventions follow the paradigm that because unhealthy lifestyle behaviours cluster together [50][51], interventions to reduce overall risk are more relevant and beneficial than individual approaches [51][52][53]. For example, research shows that 99% of smokers have additional unhealthy lifestyle behaviour such as unhealthy diet, alcohol consumption, or insufficient physical activity [50][51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These interventions follow the paradigm that because unhealthy lifestyle behaviours cluster together [50][51], interventions to reduce overall risk are more relevant and beneficial than individual approaches [51][52][53]. For example, research shows that 99% of smokers have additional unhealthy lifestyle behaviour such as unhealthy diet, alcohol consumption, or insufficient physical activity [50][51].…”
Section: Discussionmentioning
confidence: 99%
“…For example, research shows that 99% of smokers have additional unhealthy lifestyle behaviour such as unhealthy diet, alcohol consumption, or insufficient physical activity [50][51]. Moreover, evidence in the heart disease literature speaks to the benefits of multi-modal interventions focusing on diet, exercise, and stress management at improving coronary risk and psychosocial factors [52]. At the individual risk factor level, our results show that self-management interventions have a significant effect at improving medication adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Stress exposure also increases unhealthy coping behaviors such as comfort eating, smoking, excessive alcohol intake, pharmaceutical abuse and increased sedentary activity. These behaviors exacerbate psychological and physiological stress-related symptoms and increase risk for disease (9)(10)(11)(12)(13)(14)(15). There is reason to believe health disparities also contribute to stress resulting in differences in trust and engagement in the health care system (16).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has shown that overweight, eating behaviors and physical activity affect most cardiometabolic variables associated with cardiovascular risk factors, such as serum lipids, blood pressure, waist circumference and insulin resistance (2).…”
Section: Introductionmentioning
confidence: 99%